An overview of the integration and development trends between arts and psychotherapy - Xie, Yuxing; Sun, Xianhua (Frontiers in Psychology, 2025)
IntroductionIn the field of mental health, the integration of art and psychotherapy has become an important development direction. Its core mechanism lies in promoting individuals to achieve emotional release, cognitive reconstruction, and social function recovery through the creative expression of art forms, which has given rise to the important practical field of art therapy. This study aims to systematically sort out the research status and development trends in the field of art therapy from 2005 to 2024 through knowledge mapping analysis, providing references for theoretical innovation and practice standardization in this field.MethodsBased on the Web of Science core collection data sources, the CiteSpace bibliometric tool was used for knowledge mapping analysis of art therapy-related research. By searching keywords such as “Art Healing” and “Art Therapy,” 1799 valid articles were finally included after strict screening. The analysis was carried out from multiple dimensions: basic information (changes in the number of publications, journal distribution, regional and author-institution distribution) and research content (keyword co-occurrence, cluster mining, and timeline deduction).ResultsArt therapy research from 2005 to 2024 showed a phased growth characteristic, successively going through a germination period, a stable period, and a rapid development period. In terms of geographical distribution, Europe and the United States, represented by the United States and the United Kingdom, contributed 63% of the core literature. Research hotspots gradually shifted from early basic intervention research to the exploration of technological integration and ethical issues. It was also found that this field is highly related to multiple disciplines such as psychology and medicine, but there are limitations such as imbalanced development of cross-cultural theories.DiscussionAlthough significant progress has been made in the theory and practice of art therapy, there are still structural problems such as uneven development of cross-cultural theories, insufficient connection between technical applications and practice guidelines, and inadequate research coverage on special groups. Future research can focus on the in-depth integration of theory and practice, cross-cultural theoretical integration, construction of multi-dimensional evaluation systems, and application of virtual reality technology, providing new paths to promote theoretical innovation and practice standardization in art therapy.